Candidate Chemosensory Genes Identified in the Adult Antennae of Sympiezomias velatus and Binding Property of Odorant-Binding Protein 15 - Li, Xiao; Li, Jian-Wen; Sun, Wen-Xiu; Li, Wei; Gao, Hua-Yuan; Liu, Tong-Xian; Qu, Ming-Jing (Frontiers in Physiology, 2022)
Chemosensory genes play important roles in insect behaviors and have thus become potential molecular targets for pest control based on the manipulation of chemoreception-driven behaviors. The great gray weevil Sympiezomias velatus (Chevrolat) (Coleoptera: Curculionidae) is an important agricultural pest that causes serious economic losses to many crops in China, but its chemosensory genes have not been reported. Here we assembled the antennal transcriptomes of female and male adult S. velatus and revealed the major chemosensory genes necessary for olfaction. A total of 138 candidate chemosensory genes in six families were identified, including 41 encoding odorant-binding proteins (OBPs), 11 encoding chemosensory proteins (CSPs), 62 encoding odorant receptors (ORs), 15 encoding gustatory receptors (GRs), six encoding ionotropic receptors (IRs), and three encoding sensory neuron membrane proteins (SNMPs). We analyzed their phylogenetic relationship based on the amino acid sequences of these chemosensory-related protein families in S. velatus and other insects, and the expression profiles based on their antennal transcriptomes. Chemosensory genes that show antenna-abundant/specific or sex-biased expression were observed, suggesting that these genes might have functions in olfaction. Furthermore, we chose an antenna-abundant OBP belonging to ABPX subfamily, SvelOBP15, to investigate its binding property. The results showed that among 33 tested compounds, SvelOBP15 displayed high binding affinities (Ki = 7.36-12.94 μmol/L) with farnesol, nerolidol, limonene and diisobutyl phthalate, indicating that SvelOBP15 plays olfactory roles by binding and transporting specific plant volatiles. These findings will help us better understand the olfactory systems of S. velatus, and provide a basis for functional elucidation of these chemosensory genes.